Improvement Skills Writing Observation Results Report Text Through Learning Methods Cooperative Student Teams Achievement Divisions (STAD) for Students Class X TKR 1 SMKN 5 Surabaya - Cindy Afiffatus Syafi'; Rini Damayanti; Sumara Arisanthi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to improve the skills in writing text reports on observations of class This research uses the Classroom Action Research (CAR) method with 4 stages, namely planning, action, observation and reflection. The results of the research show that the Student Teams Achievement Divisions (STAD) cooperative learning method is able to improve the ability to write text reports on student observations. This is proven by the increase in grades and writing results from cycle I to cycle II. In cycle I, the lowest value was 50 and the highest is 65 with an average increase of 18%. In cycle II, the lowest value was 70 and the highest was 90 with an average increase of 29%. The conclusion of this research is that the Student Teams Achievement Divisions (STAD) cooperative learning method which is integrated with product differentiation is effective in improving the skills of writing observation report texts in class X TKR 1 SMKN 5 Surabaya students.